MANAGEMENT OF LEAN MINING AND USE OF MINERAL RESOURCES OF UKRAINE - Volkov, V.; Horoshkova, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article proposes a patent protected proprietary technique for managing lean mining and use of mineral resources of Ukraine on the example of non-metallic minerals for construction. Proposed solution of the problem on the basis of the technological relationship between the production processes and the lean use of production products with forecasting the development of the extractive industry is new. Ukraine has significant reserves of rocks suitable for mining of building stone, construction sands and expanded clay. Analysis of official statistics on the volume of mining of construction stone, construction sand and expanded clay showed that over the analyzed period, which was 12 years, there were fluctuations in both the volume of production and the rate of their growth. Approximation and smoothing of rates of growth of volumes of extraction of the investigated nonmetallic minerals for construction of a polynomial function with use of a trend line is carried out. The analysis of the obtained results showed that the fluctuations of the investigated indicators of extraction of nonmetallic minerals for construction have a periodic, cyclical nature, correlate with each other and are related to the general economic state of the construction industry and the country. It is proved that it is possible to solve the problem of lean use of minerals by more balanced extraction of minerals, namely, establishing a correlation between extraction and use volumes. To predict the development of the industry, the author suggests using multifactorial economic and mathematical model for forecasting the development of complex systems. It is proved that such a model will allow controlling the volumes of mining of technologically related minerals in interdependence on the volumes of their use.